PREGNANT LADY WITH UNDIAGNOSED HODGKIN’S DISEASE PRESENTING AS SECONDARY SCLEROSING CHOLANGITIS - Khattak, Taif; Shah, Syed Hashim Ali; Khan, Waqas; Raza, Syed Shahmeer; Ahmad, Uzair; Ullah, Farhan (Journal of Ayub Medical College Abbottabad, 2017)
Cholestatic jaundice as a paraneoplastic feature of secondary sclerosing cholangitis is rare in Hodgkin’s lymphoma. A 25 years old lady, 34 weeks primigravida was referred from the Emergency Department to the Medical Unit Khyber Teaching Hospital-MTI, Peshawar with four weeks of fever, progressive jaundice, pruritus, night sweats and weight loss. LFTs showed cholestatic picture, ERCP showed scanty intrahepatic giving beading and autumn tree appearance typical of sclerosing cholangitis. CBD was normal. Doppler U/S of hepatic and portal vein reported normal. She was started on steroids, ursodeoxycholic acid and antibiotics 3rd generation cephalosporins to which she did not respond well. This prompted a Liver biopsy which showed Hodgkin’s disease having mixed cellularity. She was shifted to specialized oncology unit for further management where she died of irreversible liver damage. This is a rare case of secondary sclerosing cholangitis in Hodgkin’s lymphoma of liver and the first case reported to our Hospital. Cholestatic jaundice as a paraneoplastic feature of secondary sclerosing cholangitis is rare in Hodgkin’s lymphoma. A 25 years old lady, 34 weeks primigravida was referred from the Emergency Department to the Medical Unit Khyber Teaching Hospital-MTI, Peshawar with four weeks of fever, progressive jaundice, pruritus, night sweats and weight loss. LFTs showed cholestatic picture, ERCP showed scanty intrahepatic giving beading and autumn tree appearance typical of sclerosing cholangitis. CBD was normal. Doppler U/S of hepatic and portal vein reported normal. She was started on steroids, ursodeoxycholic acid and antibiotics 3rd generation cephalosporins to which she did not respond well. This prompted a Liver biopsy which showed Hodgkin’s disease having mixed cellularity. She was shifted to specialized oncology unit for further management where she died of irreversible liver damage. This is a rare case of secondary sclerosing cholangitis in Hodgkin’s lymphoma of liver and the first case reported to our Hospital. Keywords: Paraneoplastic; Hodgkin’s lymphoma; Jaundice; Cholangitis